Ammonia compounds are bases in aqueous solution according to brønsted–lowry theory.
<h3>What are bases?</h3>
A base is a substance that can neutralize the acid by reacting with hydrogen ions.
Ammonia compounds are based on an aqueous solution according to brønsted–lowry theory because the water molecule donates a hydrogen ion to the ammonia, it is the Brønsted-Lowry acid, while the ammonia molecule which accepts the hydrogen ion is the Brønsted-Lowry base. Thus, ammonia acts as a base in both the Arrhenius sense and the Brønsted-Lowry sense.
Hence, ammonia compounds are based on an aqueous solution according to brønsted–lowry theory.
Learn more about the bases here:
brainly.com/question/16387395
#SPJ1
Answer:
C
) 2, 1, 2
Explanation:
The given reaction is synthesis reaction in which lithium and bromine react to form lithium bromide.
Chemical equation:
Li + Br₂ → LiBr
Balanced chemical equation:
2Li + Br₂ → 2LiBr
Step 1:
Li + Br₂ → LiBr
left hand side Right hand side
Li = 1 Li = 1
Br = 2 Br = 1
Step 2:
Li + Br₂ → 2LiBr
left hand side Right hand side
Li = 1 Li = 2
Br = 2 Br = 2
Step 3:
2Li + Br₂ → 2LiBr
left hand side Right hand side
Li = 2 Li = 2
Br = 2 Br = 2
To get moles. divide mass by molar mass.Molar mass of
Na is 23
and for Cl is 35.5.
the total molar mass of NaCl is 23+35.5 = 58.5mol/gUse the mass and divide by this number30.22g divide by 58.5mol/g and you will get 0.5166 mole.
Since the molecule has 1 Na to 1 Cl, and that the number of moles for NaCL is 0.5166. All of them would be 0.5166molesNa = 0.5166 x 1 = 0.5166molesCl = 0.5166 x 1 = 0.5166moles
to get number of atoms. Multiply your mole by Avogadro number which is 6.022x10^23Na = 0.5166 x 6.022E23 = 3.111x10^23Cl = 0.5166 x 6.022E23 = 3.111x10^23
Answer:
However, various hydrogen isotopes, such as H-2, have one proton and one neutron; H-3 has one proton and two neutrons, etc. The sum of the protons and neutrons in an atom's nucleus is its atomic mass. Thus, the atomic mass of the H-2 isotope is two, the atomic mass of the H-3 isotope is three, and so forth.
Explanation:
Answer:
MnO4⁻ (aq) + 8H⁺ (aq) + 5Fe³⁺ (aq) →Mn(aq)²⁺ + 4H2O (l) + 5Fe²⁺(aq)
Explanation:
a)
MnO4⁻ (aq) + 8H⁺ (aq) + 5e⁻ → Mn(aq)²⁺ + 4H2O (l)
b)
5Fe³⁺ (aq) +5e⁻ → 5Fe²⁺(aq)
c)
MnO4⁻ (aq) + 8H⁺ (aq) + 5Fe³⁺ (aq) →Mn(aq)²⁺ + 4H2O (l) + 5Fe²⁺(aq)